Optimizing Cellulase-Limosilactobacillus fermentum ZC529 Synergy Fermentation for Preserving Macadamia integrifolia Pericarp's Potential Use as Antioxidants - Chen Zhang; Haibo Huang; Bifan Liu; Xiongzhuo Tang; Bi'e Tan; Qian Jiang; Yulong Yin (MDPI AG, 2024)
Macadamia integrifolia pericarps (MIP) are byproducts of nut production which are rich in natural antioxidant compounds, making them an excellent source for extracting bioactive compounds. However, the antioxidant compounds in MIP are easily oxidized under natural storage conditions, resulting in significant biomass loss and resource wastage. To preserve the potential of MIP to be used as an antioxidant product, we employed cellulase and Limosilactobacillus fermentum ZC529 (L.f ZC529) fermentation and utilized response surface methodology to optimize the fermentation parameters for mitigating the antioxidant loss. Total antioxidant capacity (T-AOC) was used as the response variable. The fermented MIP water extract (FMIPE) was obtained via ultrasound-assisted extraction, and its biological activity was evaluated to optimize the best fermentation conditions. Results indicated that a cellulase dosage of 0.9%, an L.f ZC529 inoculation size of 4 mL/100 g, and a fermentation time of 7 days were the optimal conditions for MIP fermentation. Compared to spontaneous fermentation, these optimal conditions significantly increased the total phenolic and total flavonoid contents (p < 0.05). T-AOC was 160.72% increased by this optimal fermentation (p < 0.05). Additionally, supplementation with varying concentrations of FMIPE (6.25%, 12.5%, and 25%) increased the T-AOC, SOD activity, and GSH content, and reduced MDA levels of the oxidative-stressed Drosophila melanogaster (p < 0.05). Moreover, 12.5% and 25% of FMIPE treatments elevated CAT activity in the Drosophila melanogaster (p < 0.05). The effects of FMIPE on GSH and MDA in Drosophila melanogaster were equivalent to the 0.5% vitamin C (Vc) treatment. In summary, synergistic fermentation using cellulase and L.f ZC529 effectively preserves the antioxidant activity of the MIP, offering a simple, eco-friendly method to promote the utilization of MIP resources.